1982
DOI: 10.1007/bf01398933
|View full text |Cite
|
Sign up to set email alerts
|

Convexity properties of the moment mapping

Abstract: Let G be a compact Lie group, $ its Lie algebra and X a compact, connected symplectic manifold. Let G • X-~X be a Hamiltonian action of G on X and let q~: X~q* be its associated moment mapping. (See w for definitions.) The set, @(X), is the union of co-adjoint orbits. The main result of this paper is a description of the orbit structure of this set. To describe this result, we first note that the coadjoint orbits in ,q* can be parametrized as follows: Let t be a Caftan subalgebra of g and let B be a positive-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
573
1
10

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(591 citation statements)
references
References 8 publications
7
573
1
10
Order By: Relevance
“…Guillemin and Sternberg showed that the quotient of the full space by G C is equivalent to the quotient of µ −1 (0) by G [12]. In other words, (4.4b) uniquely fixes G C to G, and our moduli space is indeed the space of flat complexified connections divided by complexified gauge transformations.…”
Section: Ground States: the Geometry Of The Moduli Spacementioning
confidence: 92%
“…Guillemin and Sternberg showed that the quotient of the full space by G C is equivalent to the quotient of µ −1 (0) by G [12]. In other words, (4.4b) uniquely fixes G C to G, and our moduli space is indeed the space of flat complexified connections divided by complexified gauge transformations.…”
Section: Ground States: the Geometry Of The Moduli Spacementioning
confidence: 92%
“…Consider µ : X → t * the moment map of the T action around p. According to [12], there is a neighbourhood U ⊆ X of p and an equivariant symplectomorphism ψ : …”
Section: The Family L(1 2)mentioning
confidence: 99%
“…The main convexity result of [1] [6] is that the image under the moment map /i of a compact symplectic manifold M acted on by a torus T" is a convex polyhedron. When M is a Kahler manifold (e.g.…”
Section: Homogeneous Symplectic Manifoldsmentioning
confidence: 99%